Predicting external water pressure and cracking of a tunnel lining by measuring water inflow rate. (January 2018) - Tan, Yuqi; Smith, John V.; Li, Chun-Qing; Currell, Matthew; Wu, Yufei
Abstract: The flow of water into a tunnel, through the surrounding rock mass and the tunnel lining, has important implications for tunnel design and tunnel condition assessment. The hydraulic conductivity of the lining is a major controlling factor on the water inflow rate. Previous work had been mainly based on the assumption of constant hydraulic conductivity of the lining. In this work, the existing analytical models of water flow through a tunnel lining under steady-state, saturated conditions are extended to incorporate a linear variation of hydraulic conductivity with distance from the tunnel wall. The inhomogeneity of a lining is shown to have a significant impact on water inflow rate and water pressure distribution according to the model. The relation between lining inhomogeneity and other hydraulic parameters was established. This model can be used to predict the hydraulic pressure and crack condition at the outer face of the lining based on measured water inflow rate and the crack condition at the inner face, with significantly increased accuracy compared with the existing models based on constant hydraulic conductivity. Design charts are also developed for engineering applications.